Xylanase-Producing Microbes and Their Real-World Application - Milan Phuyal; Uttam Budhathoki; Durga Bista; Shailendra Shakya; Rajan Shrestha; Ashwinee Kumar Shrestha (International Journal of Chemical Engineering)
The present study is focused on the availability of microbial sources capable of producing xylanase, a hemicelluloses-degrading enzyme with multiple modes of action along with specificity, and their real-world applications. For the accumulation of suitable data, article surfing was carried out using multiple search engines viz. Hinari and PubMed; irrelevant and duplicate articles were discarded and articles were summarized in a narrative way herein. This review article was written aiming to bridge the recent research activities with the commercial activities of xylanase going on around the globe. The readers would be able to acknowledge themselves with the basic idea of the hydrolytic enzyme xylanase, their classification representing their different families, presenting the affinity of different families at the structural level, the sources, and the commercial implications that have been going on alone and in combination. The major hemicellulose, Xylan is digested with the help of combination other enzymes such as alpha-amylase, subtilisin, protease, and endo-1,3(4)-β-glucanase along with xylanase. Xylanase has a diverse applications such as pharmaceutical, food and feed, bakery, paper and pulp, textile, and bio-refinery industries. The objective of this review article is to compile microbial sources of this enzyme and its application for betterment of human kind.